Efeito da maré lunar na região F da ionosfera - Tsali-Brown, Vera Yesutor (2018)
The effects of the lunar tide in the F region of the ionosphere are studied in this work using measurements provided by the ionosonde installed in Cachoeira Paulista (22 ° S, 45 ° W) between 2009 and 2011. To identify the variations associated with the lunar tides, the following parameters are used: peak height of electronic density of the F region (hmF2) and the critical frequency of the F (foF2) region. The influence of the lunar tide in the Brazilian ionosphere was obtained using the residual measurements which was without the influence of the solar tide for each day, owing that all the months were converted to the lunar time and submitted to harmonic analysis to obtain monthly amplitudes and phases for the period of study. The maximum diurnal amplitude in foF2 determined was 0.41MHz and 0.42MHz in the semidiurnal component. Also the maximum diurnal amplitude in hmF2 determined was 6.25km and semidiurnal 7.76km. The seasonal variations in the amplitudes in foF2 and hmF2 were sometimes annual and semiannual in nature.